Multi Evaluation of a Modified GoldNano Carb Test for Carbapenemase Detection in Clinical Isolates of Gram-Negative Bacilli - Arpasiri Srisrattakarn; Aroonlug Lulitanond; Nicha Charoensri; Lumyai Wonglakorn; Suthida Kenprom; Chutipapa Sukkasem; Waewta Kuwatjanakul; Sirikan Piyapatthanakul; Onphailin Luanphairin; Wichuda Phukaw; Kunthida Khanchai; Jantira Pasuram; et al. (MDPI AG, 2022)
Carbapenemase-producing Gram-negative bacteria have been increasingly reported. Simple and sensitive methods for carbapenemase detection are still needed. In this study, a gold nanoparticle (AuNP) solution was modified by the addition of zinc sulfate (ZnSO4) for improving the conventional GoldNano Carb (cGoldC) test, and the modified GoldC (mGoldC) test was then evaluated for phenotypic detection of carbapenemase production in Gram-negative bacilli clinical isolates. ZnSO4 was added to give final concentrations of 0.25, 0.5, 0.75, and 1 mM. The performance of the mGoldC test was evaluated in Enterobacterales, Acinetobacter spp., and Pseudomonas aeruginosa isolates from six hospitals in different regions using polymerase chain reaction (PCR) as a gold standard. The AuNP solution with 0.25 mM ZnSO4 was used for the mGoldC test. Evaluation of the mGoldC test in 495 Enterobacterales, 212 Acinetobacter spp., and 125 P. aeruginosa isolates (including 444 carbapenemase producers and 388 non-carbapenemase producers) revealed sensitivity, specificity, a positive likelihood ratio, and a negative likelihood ratio of 98.6%, 98.2%, 54.7, and 0.01, respectively. This test is fast, easy to perform, cost-effective (~0.25 USD per test), and highly sensitive and specific for routine carbapenemase detection, thus leading to effective antimicrobial therapy and infection control measures.